Development and validation of fast duplex real-time PCR assays based on SYBER Green florescence for detection of bovine and poultry origins in feedstuffs. (15th April 2015) - Safdar, Muhammad; Junejo, Yasmeen
Highlights: A duplex real-time PCR assay for bovine and poultry species detection in feedstuffs. We report the assay which saves cost, time, and materials. We report the assay has high specificity and sensitivity. We report the assay for detection of animal species in feedstuffs. SYBER Green dye based assay is cheaper than probe-based methods. Abstract: SYBR duplex real-time polymerase chain reaction (SDRT-PCR) with melting curve analysis was developed that can unite the reward of multiplex PCR with real-time PCR to recognize animal genes rapidly in feedstuffs. The method merges the use of bovine ( Bos taurus ) and poultry ( Gallus gallus ) specific primers that amplify small fragments (amplicons <200 base pairs) of the mitochondrial gene. Appropriate mixtures of bovine and poultry heat treated meat DNAs were used to develop the assay. Gene products of bovine and poultry were produced two distinct melting peaks simultaneously at 79.5 °C and 87.5 °C, respectively. Multiplex analysis of the reference feed samples showed that the detection limit of the assay was 0.001% for bovine and poultry species. Based upon the assay results it has been concluded that SDRT-PCR assay might be an efficient tool for the verification of species origin in feedstuffs.